Second Person in Different Genres and Cultural Practices - Joanna Jeziorska-Haładyj; Magdalena Rembowska-Płuciennik (Zagadnienia Rodzajów Literackich)
The editorial introduction shows the richness of traditional literary genres (fictional and non-fictional), new cultural practices (digital literature, games, and playable media) in which second-person address may be encountered. The presence of a direct address to “you” (individual or collective) is also a distinct marker of contemporary marketing, advertising, and social media communication. There is a number of transitional forms in-between print and digital literature and games, in which the presence of the second-person pronoun is one of the main features of poetics. These include narrative role-playing games (RPGs), game books, interactive text games, and paragraph games/books. Complementing the existing gap in Polish interdisciplinary research, the editors discuss both the historical forms of second-person narrative and its potential to cross the boundaries between various media. Additionally, the article reconstructs the fuzzy status of you-narrative in 20th-century narrative theory, since the semantic ambiguities of the multifaceted “you” address resulted in multiple theoretical attempts at defying and analyzing the second-person storytelling. We summarize the main threads of the heated debate on the semantics, poetics, and pragmatics of second-person narrative that took place at the turn of the 20th and 21st centuries. The editorial discusses the reasons why narrative theory gradually recognized the typological equivalence of second-person storytelling to the third- and first-person narrative mode. Another recurring problem in research on second person is its impact on reader’s immersion and identification processes. Moreover, we indicate the new cultural context (the digital revolution) as an important factor in the current dissemination and popularization of second-person narratives.